2020
DOI: 10.1007/s13238-020-00694-x
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitors overcome immunotherapy resistance in B-cell lymphoma

Abstract: Immunotherapy has been applied successfully to treat B-cell lymphomas in preclinical models or clinical settings. However, immunotherapy resistance is a major challenge for B-cell lymphoma treatment. To overcome this issue, combinatorial therapeutic strategies have been pursued to achieve a better efficacy for treating B-cell lymphomas. One of such strategies is to combine immunotherapy with histone deacetylase (HDAC) inhibitors. HDAC inhibitors can potentially increase tumor immunogenicity, promote anti-tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 98 publications
1
45
0
Order By: Relevance
“…Histone acetylation can be regulated by acetyl-CoA from different sources in different cell conditions (Sivanand et al, 2018 ). HDACs, responsible for the removal of acetyl groups from histone lysine residues, have been reported to have abnormal expression in cancers, and HDAC inhibitors (HDACi) have been considered as potential drugs in cancer treatment (Audia and Campbell, 2016 ; Li and Seto, 2016 ; Peleg et al, 2016 ; San Jose-Eneriz et al, 2019 ; Mirzaei et al, 2020 ; Wang P. et al, 2020 ; Wang X. et al, 2020 ).…”
Section: Amino Acid Metabolism and Epigeneticsmentioning
confidence: 99%
“…Histone acetylation can be regulated by acetyl-CoA from different sources in different cell conditions (Sivanand et al, 2018 ). HDACs, responsible for the removal of acetyl groups from histone lysine residues, have been reported to have abnormal expression in cancers, and HDAC inhibitors (HDACi) have been considered as potential drugs in cancer treatment (Audia and Campbell, 2016 ; Li and Seto, 2016 ; Peleg et al, 2016 ; San Jose-Eneriz et al, 2019 ; Mirzaei et al, 2020 ; Wang P. et al, 2020 ; Wang X. et al, 2020 ).…”
Section: Amino Acid Metabolism and Epigeneticsmentioning
confidence: 99%
“…Activation of the immune response by HDACi could also be an effective innate method to prevent cancer relapse when administered in a regimen with immunotherapeutic ( Guerriero et al, 2017 ; Wang X. et al, 2020 ). The class IIa HDACi TMP195 efficiently improves the durability of tumor reduction in breast cancer by strengthening the phagocytic role of macrophages that are involved in the IFNγ axis; it also activates the adaptive anti-tumor immune response.…”
Section: Hdac Inhibitors In Cancer Therapymentioning
confidence: 99%
“…In addition to its direct anticancer activity, HDACi has pleiotropic immunomodulatory effects (31)(32)(33). HDACi can enhance the intratumoral infiltration of CD8+ T cells and macrophages, decrease the intratumoral infiltration of T-regulatory cells, myeloid-derived suppressor cells, and protumorigenic M2 macrophages, induce the intratumoral expression of multiple chemokines, upregulate the expression of MHC and co-stimulatory molecules, enhance immune recognition, promote tumor-specific T cell-mediated killing of cancer cells, and sensitize tumor cells to NK cell lysis (32,(34)(35)(36)(37)(38)(39)(40)(41)(42). Preclinical studies have demonstrated that HDACi can enhance the anticancer activity of immunotherapy in several types of cancers (36,37,(43)(44)(45).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%